A Comparison of Three Asian English Textbooks by Correspondence Analysis - Uenishi, Koji (Archives of Business Research, 2024)
This paper explores the differences of the English textbooks for the fifth graders in China, Myanmar, and Sri Lanka in Asia. Specifically, the fifth graders’ textbooks were analyzed using a readability tool and Correspondence Analysis (hereafter, CA). An analysis of the data suggests that, in terms of readability and content, there were both similarities and differences between the three textbooks. More precisely, regarding readability, the English textbook of China is closer to the level of English textbook of Myanmar, and the level of textbook of Sri Lanka is higher than the other two textbooks. Also, concerning the content including vocabulary, CA shows that basically the three textbooks are different from each other.